1980
DOI: 10.1002/pol.1980.170180102
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose organic solutions: A nuclear magnetic resonance investigation

Abstract: Four solvents of cellulose have been studied by using 13C‐NMR spectroscopy. All these solvents, N‐methyl morpholine‐N‐oxide, methylamine, hydrazine, and paraformaldehyde (PF), contained dimethyl sulfoxide (DMSO) as a cosolvent. Oligomers of cellulose of DP = 10 soluble in hot DMSO have been used as model compounds. 13C chemical shifts and line shapes show that three of the mentioned solvents are “true solvents” of cellulose. On the other hand, dissolution of cellulose in DMSO‐PF system occurs by the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 17 publications
3
22
0
1
Order By: Relevance
“…A peak at 81.8 ppm and a doublet peak at 78.3 ppm (in total three carbon peaks) cannot be assigned .explicitly due to the heavy overlapping of the proton peaks at 3.57 ppm which are directly correlated with the above three carbon peaks. The above assignment carried out here for 13 C peak is, as far as C 1 , C 2 , and C 6 carbon peaks are concerned, in good coincidence with those by Gagnaire et al 2 for cellulose oligomer/ DMSO-d 6 system and by Nardin and Vincendon 15 for cellulose/DMAC/LiCl system. Figure 7(a) shows the 1 H 1D-NMR spectrum of CT A/TCM-d system.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…A peak at 81.8 ppm and a doublet peak at 78.3 ppm (in total three carbon peaks) cannot be assigned .explicitly due to the heavy overlapping of the proton peaks at 3.57 ppm which are directly correlated with the above three carbon peaks. The above assignment carried out here for 13 C peak is, as far as C 1 , C 2 , and C 6 carbon peaks are concerned, in good coincidence with those by Gagnaire et al 2 for cellulose oligomer/ DMSO-d 6 system and by Nardin and Vincendon 15 for cellulose/DMAC/LiCl system. Figure 7(a) shows the 1 H 1D-NMR spectrum of CT A/TCM-d system.…”
supporting
confidence: 90%
“…The assignment given by Gagnaire et al 2 for cellulose can be considered reasonable in DMSO-d6 ; however, mention should be made of the assignment of peaks in other solvents: it could not always be done, by referring to their assignment straightly, because Cs, C 3 , and C 2 peaks of cellulose oligomer in DMSO-d 6 were located very close to each other and the order of the peak positions may possibly to change in other solvents. In addition, note that the positions of the ring carbon peaks are significantly influenced by substitution of hydroxyl groups in cellulose derivatives, for which the assignment for cellulose by Gagnaire et al cannot be straightforwardly applied as it is and the methods proposed hithertofor in analysis of NMR spectra of cellulose derivatives are without exception too elaborate and timeconsuming and additionally they are not sufficiently accurate.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…From Figure 2A, PCLA shows hydrocarbon around 1.38-2.32 and 4.01-4.35 ppm, methylene around 5.89-5.91 and 6.34-6.38 ppm and hypo-methylene around 6.12-6.19 ppm. The proton spectrum of EC-g-PCLA ( Figure 2D) shows the peaks of EC 16 ( Figure 2B) and shows methylene and hypo-methylene of PCLA. 17 It also shows methyl of TDI resonance at 2.19 ppm, and benzene ring resonance at 7.04-7.47 ppm from NCOPCLA in Figure 2C.…”
Section: Synthesismentioning
confidence: 99%
“…The NMMO dissolution technique is well established for producing regenerated cellulose, with an output of 220 kilotons/year of Lyocell fibers. NMR analyses have shown that neither cellulose derivation nor cellulose complex formation takes place with NMMO (Gagnaire et al 1980). Fink et al (2001) has reviewed the structure formation of regenerated cellulose materials from NMMO solutions.…”
Section: Introductionmentioning
confidence: 99%